Core temperature assessment by CorTempTM during and following an English professional soccer match - Clark, N.; Edwards, A. M.; Cooke, C. B. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Core temperature is known to increase during exercise and the magnitude of this increase is determined by the relative stress of the exercise, the environmental conditions and hydration status (Saltin and Costill 1988). Due to technical limitations associated with the measurement esophageal and rectal temperatures in field based contact sports (O'Brien et al. 1998), few studies have reported core temperature either during or immediately following professional soccer match performance. The aim of this study was therefore to identify a practical method of core temperature assessment in response to match play. Methodology Seven healthy 1st team male soccer players (age = 24 ± 3 years, body mass = 74.4 ± 4 kg, height 179 ± 4 cm) from a professional English Division One team agreed to participate in this study. Data was collected from a pre-season match against English Premier League opposition. Four hours prior to the match all players ingested a telemetric temperature pill (Tpill)(CorTempTM, Human Technologies Inc) which consists of a temperature sensitive quartz crystal oscillator with a silver oxide battery, encapsulated in epoxy and covered with silicone rubber. The telemetric signals were received and stored by a data logger and downloaded to a computer after completion of data collection. Atmospheric conditions remained stable over the course of the match (19° C and 765 mmHg). Blood samples were taken pre and post match for the assessment of Hct, Hb, blood lactate concentrations and plasma volume. All tests were taken at resting state one hour prior to the game and players were tested again immediately following the conclusion of the match. Four players agreed to core temperature assessment at half-time but the remaining three players were unavailable while receiving tactical instruction from the coaching staff. Statistical analysis was performed using student paired tests. Results Tpill increased significantly pre to post match in all (n=7) players (36.9 ±0.5 °C to 38.6 ±0.6 °C) (P<0.01) and showed a trend for increased Tpill from half-time (38.1 ±0.3 °C) to full-time (38.8 ±0.5 °C) (n=4) (P<0.1).Body mass and plasma volume both significantly decreased pre to post match (Body mass - 1.9 % decrease and plasma volume 11.6 % decrease) (P<0.01). Blood lactate concentrations increased significantly from resting to half-time (1.2 mmol·l-1 ±0.3 mmol·l-1 and 4.7 ±0.6 mmol·l-1) (P<0.01) but were not different from half-time to full-time (4.5 ±0.8 mmol·l-1). Discussion The telemetry thermometer pill provided a novel and acceptable alternative assessment of core temperature during match play in professional soccer players. All players were able to swallow the pill and did not report any adverse effects or perceptions before, during or after the game. It is now accepted that that any degree of dehydration impairs physiological function and thermoregulation. English professional soccer players often experience significant dehydration of 2% or more when playing (Davies et al. 1997), which has been shown to impair physical and mental performance (Gopinathan et al. 1988). However, the individual response of players is difficult to predict, which means that in practice players need to be individually assessed in order to be able to understand their thermoregulatory responses to the requirements of professional soccer. Repeated individual assessments can then be made to establish an appropriate strategy for avoiding or diminishing dehydration and the associated negative effects on physical and mental performance. A fluid loss of 1% of body mass significantly increases core temperature, which was also shown in this study. Like dehydration, changes in core temperature have been shown to be variable among individuals. The measurement of core temperature therefore provides a useful additional measure in characterising the individual variation in thermoregulatory responses to professional soccer.